HeRbS : an A-Z guide GARDENING, COOKING & HEALTH - Allardice, Pamela; Allardice, Pamela; Barrett, Keran; Bitcon, Georgina; Flew, Janine; Lewis, Lynn; McDonald, Debbie; A. McLeod, Judith, Dr.; Rich, Cathryn; Tancred, Jayne; Wheatley, Gabrielle; McPhee, Margaret; et al. (Ultimo, NSW : Reader's Digest, 2013)
Herbs are the most hardworking of plants. They have been used for thousands of years to flavour and preserve food, treat ailments, ward off pests and diseases, freshen the air, and decorate and enhance our lives. Over the centuries, they have also become associated with fascinating myths and folklore. This practical directory provides information on how to grow, harvest and store herbs and how to make the best use of them in your daily life. You'll find recipes, homemade beauty products, safe herbal remedies and ways to make and use herbal cleaning products in the home
Includes index
Keywords: Herbs; Herb gardening; Herbs -- Utilization